PENGEMBANGAN MODUL AJAR BERDIFERENSIASI DALAM PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SDN 02 KANIGORO - Risa Kholud Andriana; Ma'rufah Rohmanurmeta, Fauzatul; Puji Astuti, Atik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this research is to produce a valid, practical, and effective differentiated teaching module on the Pancasila Education that can be used by teachers in the process of teaching and learning activities. The research used a type of Research and Development (R&D) research using the 4-D development model which consists of several stages, namely Define, Design, Develop, and Disseminate. Data was collected through expert validation techniques, teacher response questionnaires, and pretest-posttest. The results showed that the development of differentiated teaching modules was declared very valid with an average score of 86.33% from the validator team. The results of the teacher response questionnaire obtained a score of 91.4% with very practical criteria. While the results of the n-gain test analysis obtained an average score of 0.54 with moderately effective criteria. Thus, the results of the product development of differentiated teaching modules are very valid, very practical, and quite effective and can be used by teachers as teaching tools on the Pancasila Education in grade IV.